Pathogenicity and non-opportunistic character of Blastocystis spp.: a hospital-based survey in Central Cameroon - Stéphanie Jupsa-Mbiandou; Samuel Fosso; Edimo Billé; Tito T Mélachio-Tanekou; Gideon Ajeagah-Aghaindum; Hugues C Nana-Djeunga; Albert Samé-Ekobo; Flobert Njiokou (Journal of Infection in Developing Countries)
Introduction: Blastocystis spp. is a protist found in humans. Although usually the most frequent protozoa found in stool samples of both symptomatic and healthy subjects, its pathogenic or rather opportunistic role is yet to be clearly elucidated. To attempt to fill this gap, a cross-sectional study was conducted to compare the frequency of Blastocystis spp. in HIV positive (HIV+) versus HIV negative (HIV-) individuals in four health facilities of the Center Region of Cameroon.